Physically based modeling, characterization and design of an induction hardening process for a new slurry pipeline steel. (15th November 2019) - Javaheri, Vahid; Pohjonen, Aarne; Asperheim, John Inge; Ivanov, Dmitry; Porter, David
Abstract: Numerical and Gleeble experimental data are combined to predict potential microstructure and hardness profiles through the wall thickness of an induction hardened slurry transportation pipe made of a recently developed 0.4 wt% C, Nb-microalloyed steel. The calculated thermal history of various positions through the wall thickness of an industrial pipe (400 mm diameter, 10 mm thick) were combined with a model that predicts the phase transformations, microstructures and final hardness values on heating and cooling along arbitrary thermal cycles. The accuracy of the hardness profile predictions was verified by experimental data, i.e. reproducing the thermal cycles on a Gleeble thermomechanical simulator. The results indicated that the approach should be a feasible way to optimize induction heating and cooling parameters to obtain desired hardness profiles through the wall thickness. Graphical abstract: Unlabelled Image Highlights: An empirical model has been developed for prediction of phase fraction of a new steel after different cooling rates. The model has been coupled with the simulated thermal history to predict the microstructure of each pipe thickness layers. The effect of heating rate on the austenitization critical temperatures has been considered to the model. The simulation shows slightly faster austenitization kinetics probably due to neglecting the effect of grain size. The model can be used to optimize the hardness or microstructure gradient based on the industrial considerations. The designed thermal cycles produced a gradient of material properties giving ∼3 mm hardening depth in a 10 mm thick pipe.